Effects of a 3D-printed orthosis compared to a low-temperature thermoplastic plate orthosis on wrist flexor spasticity in chronic hemiparetic stroke patients: a randomized controlled trial. (February 2020) - Zheng, Yanan; Liu, Gongliang; Yu, Long; Wang, Yanmin; Fang, Yuan; Shen, Yikang; Huang, Xiuling; Qiao, Lei; Yang, Jianzhong; Zhang, Ying; Hua, Zikai
Objective: The aim of this study was to compare the effects of two kinds of wrist-hand orthosis on wrist flexor spasticity in chronic stroke patients. Design: This is a randomized controlled trial. Setting: The study was conducted in a rehabilitation center. Participants: A total of 40 chronic hemiparetic stroke patients with wrist flexor spasticity were involved in the study. Interventions: Patients were randomly assigned to either an experimental group (conventional rehabilitation therapy + 3D-printed orthosis, 20 patients) or a control group (conventional rehabilitation therapy + low-temperature thermoplastic plate orthosis, 20 patients). The time of wearing orthosis was about 4–8 hours per day for six weeks. Main measures: Primary outcome measure : Modified Ashworth Scale was assessed three times (at baseline, three weeks, and six weeks). Secondary outcome measures : passive range of motion, Fugl-Meyer Assessment score, visual analogue scale score, and the swelling score were assessed twice (at baseline and six weeks). The subjective feeling score was assessed at six weeks. Results: No significant difference was found between the two groups in the change of Modified Ashworth Scale scores at three weeks (15% versus 25%, P  = 0.496). At six weeks, the Modified Ashworth Scale scores (65% versus 30%, P  = 0.02), passive range of wrist extension ( P  < 0.001), ulnar deviation ( P  = 0.028), Fugl-Meyer Assessment scores ( P  < 0.001), and swelling scores ( P  < 0.001) showed significant changes between the experimental group and the control group. No significant difference was found between the two groups in the change of visual analogue scale scores ( P  = 0.637) and the subjective feeling scores ( P  = 0.243). Conclusion: 3D-printed orthosis showed greater changes than low-temperature thermoplastic plate orthosis in reducing spasticity and swelling, improving motor function of the wrist and passive range of wrist extension for stroke patients.